Inteligencia Emocional en los procesos de aprendizaje en los estudiantes de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo. - Moya López, Vicky Alejandra (2024)
The main objective of the following research work was to determine the relationship between emotional intelligence and learning processes in students of the Psychopedagogy career at the National University of Chimborazo, taking into account that emotional intelligence is a critical factor for the personal development of an individual and also the interpersonal relationships they have in any environment, while the learning process involves: a succession of academic-type activities that are measured by a grade. The methodology had a quantitative approach with a non-experimental design; due to its scope, it is correlational, due to the objectives, basic, due to the field location and transversal time, having as the study population the students of the Psychopedagogy career and as sample selected in the second and sixth semester of said degree; The psychometric technique of the Emotional Intelligence Scale was used: Trait Meta-Mood Scale (TMMS-24) with its respective instrument and the report card with a quantitative scale, under three levels: excellent, very good and reasonable. The Excel program was used to carry out the analysis and interpretation of the results. In contrast, statisticians were used to create graphs for both emotional intelligence and learning processes, and the SPSS program was used to correlate the variables. It is concluded in such a way that both men and women have good levels of attention, clarity, and emotional repair. Likewise, their learning process is perfect, with both study variables positively correlated.